Seasonal Changes in Mineral and Trace Elements of Çanak Cheese - Kirdar, S.S.; Ocak, E.; Kose, S.; Ozer, E. (Asian Journal of Chemistry, 2013)
Seasonal changes of the ash content and mineral concentrations in Çanak cheese were studied. Mineral, trace and heavy metals including calcium, potassium, magnesium, copper, manganese, iron and zinc were analyzed using atomic absorption spectrometry. At the end of the study, the ash content averaged 3.85 ± 0.26 % in the winter samples and 3.00 ± 0.14 % in the summer ones. The mean concentration of 63,92, 296,74 and 1571,60 mg/kg (in winter) and 56,69, 225,61 and 1221.46 mg/kg (in summer) were measured for Mg, K and Ca, respectively. The concentration of the tested metals was in the range Zn > Fe > Cu > Mn over two seasons. Differences in mineral contents in the cheese making season was statistically significant (p < 0.01) significant seasonal variation was found for Ca, K, Mn and Fe (p < 0.01).